Preparation and properties of magnetic nano- and microsized particles for biological and environmental separations - Horák, Daniel; Babic, Michal; Macková, Hana; Benes, Milan J (Journal of separation science, 2007)
The paper presents a critical overview on magnetic nanoparticles and microspheres used as separation media in different fields of chemistry, biochemistry, biology, and environment protection. The preparation of most widely used magnetic iron oxides in appropriate form, their coating or encapsulation in polymer microspheres, and functionalization is discussed in the first part. In the second part, new developments in the main application areas of magnetic composite particles for separation and catalytical purposes are briefly described. They cover separations and isolations of toxic inorganic and organic ions, proteins, and other biopolymers, cells, and microorganisms. Only selected number of relevant papers could be included due to the restricted extent of the review.
Keywords: Environmental Pollutants; povrchové vlastnosti; látky znečišťující životní prostředí; biologické přípravky; Surface Properties; Biological Products; Phase Transition; změna skupenství; magnetismus; Nanoparticles; Magnetics; nanočástice